Robotic and Advanced Laparoscopic Surgical Training in European Gynecological Oncology Trainees. Issue 2 (1st February 2017) - Gan, Carmen; Bossart, Michaela; Piek, Jurgen; Halaska, Michael; Haidopoulos, Dimitrios; Zapardiel, Ignacio; Grabowski, Jacek P.; Kesic, Vesna; Kimmig, Rainer; Cibula, David; Lambaudie, Eric; Verheijen, Rene; et al.
Abstract : Introduction: Advanced minimal access surgical training is an important component of training in gynecological oncology (GO). Europe-wide data on this topic are lacking. We present data on availability and trainee experience of advanced laparoscopic surgical (ALS) and robotic surgical (RS) training in GO across Europe. Method: A prospective web-based anonymized survey of European GO trainees was sent to the European Network of Young Gynaecological Oncologists members/trainees. It included sociodemographic information and specific questions pertaining to training experience or satisfaction in laparoscopic and robotic surgery. χ 2 test was used for evaluating categorical variables and Mann-Whitney/Kruskal-Wallis (nonparametric) tests for continuous variables between 2 and more independent groups. Results: A total of 113 GO trainees from 29 countries responded. The mean (standard deviation) age was 35.2 (6.1) years, 59.3% were men, 40.7% were women, and 46% were in accredited training posts. The ALS and RS training was offered in only 43% and 23% of institutes respectively, and 54% and 23% of trainees had undergone some form of formal or informal training in ALS and RS respectively. A total of 62.4% felt that RS should be a formal component of GO training programs. A total of 61% and 35% planned to go outside their institute for ALS or RS training respectively. Trainees rating (1–5 scale) of their open surgery and ALS or RS skills (3.3/2.6/1.9) and training experience (3.5/2.8/2.1), respectively, were higher for open surgery than ALS or RS ( P < 0.0005). Accredited posts were more likely than nonaccredited posts to offer ALS training (60%/31%, P = 0.002), formal training schedules (27.9%/4.4%, P = 0.003), and use of logbooks (46%/23%, P = 0.035). Conclusions: Training and experience in ALS and RS are poorly rated by GO trainees across Europe, and only few centers offer this. There is an urgent need to expand and harmonize training opportunities for ALS and RS. Most trainees want RS included as a formal component of their training.